Domestic Violence Against Women, a Major Health Probelm-Focus on the Causes and Effects : a case study of kitumba parish, Muterere sub county, Bugiri district - Awori, Joyce (Kampala : Uganda Christian University, 2007)
Descriptive Cataloging Uganda Christian University
Keywords: Domestic Violence -- Causes and effects -- Uganda, Bugiri District